Discovery of Icotinib-1,2,3-Triazole Derivatives as IDO1 Inhibitors - Mao, Long-fei; Wang, Yu-wei; Zhao, Jie; Xu, Gui-qing; Yao, Xiao-jun; Li, Yue-Ming (Frontiers in Pharmacology, 2020)
Tumor immunotherapy is considered to be a highlight in cancer treatment in recent years. Indoleamine 2,3-dioxygenase 1 (IDO1) is closely related to the over expression of many cancers, and is therefore a promising target for tumor immunotherapy. To search for novel IDO1-targeting therapeutic agents, twenty-two icotinib-linked 1,2,3-triazole derivatives were designed, synthesized and evaluated for their IDO1inhibitory activity. The structures of synthesized compounds were confirmed by 1H NMR, 13C NMR and HR MS. IDO1 inhibitory activity assay results indicated that ten of those compounds have remarkable inhibitory activity against IDO1, among which compound a17 was the most potent with IC50 of 0.37 M. Molecular modeling revealed the potential binding model between the compounds and IDO1, and a direct relationship between a compound’s bonding strength and its IDO1inhibitory activity. These observations suggest that icotinib-1,2,3-triazole derivatives are potential competitive inhibitor that preferentially binds to the active ferrous form of IDO1 by forming a coordinate bond with the haem iron.